Musa paradisiaca L. leaf and fruit peel hydroethanolic extracts improved the lipid profile, glycemic index and oxidative stress in nicotinamide/streptozotocin‐induced diabetic rats - Ahmed, Osama M. (Vet Med Sci, 2020)
This study aimed to assess antihyperlipidemic, cardiac and antioxidant effects as well as mode of actions of Musa paradisiaca (M. paradisiaca) leaf and fruit peel hydroethanolic extracts in nicotinamide (NA)/streptozotocin (STZ)‐induced diabetic rats. Experimental diabetes mellitus was induced by a single intraperitoneal injection of STZ (60 mg/kg body weight), 15 min after intraperitoneal injection of NA (120 mg/kg body weight). NA/STZ‐induced diabetic rats were orally supplemented with M. paradisiaca leaf and fruit peel hydroethanolic extracts in a dose of 100 mg/kg body weight/day for 28 days. The treatment of NA/STZ‐induced diabetic rats with M. paradisiaca leaf and fruit peel extracts significantly decreased the elevated fasting and post‐prandial serum glucose, total cholesterol, triglycerides, LDL‐cholesterol and vLDL‐cholesterol levels and significantly increased the lowered serum insulin level, liver glycogen content, serum HDL‐cholesterol level, homeostasis model assessment‐insulin resistance (HOMA‐IS) and HOMA‐β cell function. The elevated cardiovascular risk indices in diabetic rats were significantly improved due to treatment with M. paradisiaca extracts. Concomitant with the increase in liver glycogen content, the glucose‐6‐phosphatase activity significantly decreased reflecting the decrease in hepatic glucose output. The heart function was potentially ameliorated as manifested by decrease in the elevated serum creatine kinase‐MB, lactate dehydrogenase and aspartate aminotransferase activities after treatments of diabetic rats with M. paradisiaca extracts. The elevated liver lipid peroxidation and the decline in liver glutathione content and superoxide dismutase, glutathione peroxidase and glutathione‐S‐transferase activities were significantly reversed by treatments. Thus, it can be concluded that M. paradisiaca leaf and fruit peel hydroethanolic extracts may have antihyperlipidemic and cardioprotective potentials in NA/STZ‐induced diabetic rats. These effects may be mediated via improvements in the glycemic state, β‐cell function, tissue insulin sensitivity, and antioxidant defense mechanism.